2009
DOI: 10.1101/gad.1735109
|View full text |Cite
|
Sign up to set email alerts
|

Robust production and passaging of infectious HPV in squamous epithelium of primary human keratinocytes

Abstract: Using Cre-loxP-mediated recombination, we established a highly efficient and reproducible system that generates autonomous HPV-18 genomes in primary human keratinocytes (PHKs), the organotypic raft cultures of which recapitulated a robust productive program. While E7 promoted S-phase re-entry in numerous suprabasal differentiated cells, HPV DNA unexpectedly amplified following a prolonged G2 arrest in mid-and upper spinous cells. As viral DNA levels intensified, E7 activity diminished and then extinguished. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

22
220
2
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 161 publications
(245 citation statements)
references
References 49 publications
22
220
2
1
Order By: Relevance
“…HPV cannot be cultured but only recently, an efficient virus propagation in vitro has been introduced [6]. HPVs infect undifferentiated basal cells of epithelia after trauma or erosion, and are maintained there at a low copy number.…”
Section: Hpv Life Cyclementioning
confidence: 99%
“…HPV cannot be cultured but only recently, an efficient virus propagation in vitro has been introduced [6]. HPVs infect undifferentiated basal cells of epithelia after trauma or erosion, and are maintained there at a low copy number.…”
Section: Hpv Life Cyclementioning
confidence: 99%
“…Papillomavirus are highly species-specific, making animal models for HPV difficult to obtain, except by using animal papillomavirus. Even though these difficulties in finding experimental models of HPV infection and carcinogenesis have been largely overcome during the first years of the new century, with the development of HPV-transfected organotypic cell cultures [2], research on animal papillomavirus, and particularly on BPV, does not seem to have diminished since then. This review will deal with selected recent literature on animal papillomavirus, especially with those papers published over the last two years.…”
Section: Introductionmentioning
confidence: 99%
“…Using tissue sections from time course experiments, we have determined a temporal order of the HPV productive program by fluorescence in situ hybridization detection of viral DNA amplification (DNA-FISH), concurrently with antibody detection of BrdU incorporation and E7-induced cellular proteins or viral proteins, as well as by DAPI staining of nuclei. 8 These then stably accumulated in the cornified envelopes (Fig. 1B and data not shown).…”
mentioning
confidence: 99%
“…In Wang et al 2009, 8 we reported a simple yet efficient and reproducible approach which overcame the limitations of the methods heretofore used by other investigators in the HPV field. We have recapitulated an exceptionally productive program in PHK raft cultures.…”
mentioning
confidence: 99%
See 1 more Smart Citation